Factors affecting tacit knowledge transfer within an organization - Liu, Su Hung (Universiti Malaysia Sarawak, (UNIMAS), 2011)
This research paper aims to identify the relevant factors for tacit knowledge transfer within a public utility organization -Sarawak Energy Berhad (SEB) and to determine the demographic classification of SEB staff and their perception towards tacit knowledge transfer within their workplace. The methodology in this research analyses the literature concerning tacit knowledge transfer within organizations and using a quantitative approach based on exploratory factorial analysis. It seeks to collect facts in order to identify relevant factors for tacit knowledge transfer within the organization studie~ The research findings demonstrated that four most relevant factors affecting tacit knowledge transfer within an organization are knowledge management strategy, work culture and environment, individual traits and organizational structure and there is no significant different generally on the employees' perception on tacit knowledge transfer based on their demographical factors. One of the limitations on the research is that the research is done on SEB that causes the external validity cannot be tested. Another limitation is the subjective perception of the employees involved in relation to tacit knowledge transfer. The lack of information available while answering the questionnaire and the fact that the respondents work in a state..owned, rather than a public or private company may lead to the biased perception of the respondents. The value of the study is that the factors affecting tacit knowledge transfer identified are useful for further study in implementing the tacit knowledge management on its transferring program for SEB and other similar organizations.